Aorto‐Right Atrial Fistula at Aortotomy Site Following Surgical Myectomy. Issue 9 (13th September 2013) - Kalra, Ankur; Kohl, Louis P.; Asinger, Richard W.; Bachour, Fouad A.; Van Camp, Joseph R.; Ayenew, Woubeshet; Bart, Bradley A.
Mini‐Abstract Aorto‐right atrial fistula (A‐RAF) is a rare condition that has been reported as a postsurgical complication following cardiac surgery. Diagnosing A‐RAF can be challenging, and requires a high index of suspicion. In our patient, following surgical myectomy for hypertrophic cardiomyopathy, aortic dissection occurred at the aortotomy site that was then contained by postsurgical adhesions, leading to formation of A‐RAF.